Examining the Relationship of Clinical and Laboratory Parameters With Infectiousness to Phlebotomus perniciosus and Its Potential Infectivity in Dogs With Overt Clinical Leishmaniasis - Gizzarelli, Manuela; Bosco, Antonio; Foglia Manzillo, Valentina; Bongiorno, Gioia; Bianchi, Riccardo; Giaquinto, Daniela; Ben Fayala, Nour El Houda; Varloud, Marie; Crippa, Alessia; Gradoni, Luigi; Cringoli, Giuseppe; Maurelli, Maria Paola; et al. (Frontiers in Veterinary Science, 2021)
Infected dogs are considered the main domestic animal reservoirs for Leishmania infantum parasite. Infectiousness to competent phlebotomine vectors has been associated with many factors, the main being the severity of the disease exhibited by infected dogs. This study examines the relationship between different clinical parameters and the infectiousness to colonized Phlebotomus perniciosus sand flies having a blood meal on dogs. Data obtained in the present study come from an untreated group of Leishmania sick dogs submitted to xenodiagnosis for the evaluation of a spot on insecticide solution. Seventeen dogs were diagnosed as affected by leishmaniasis through clinical examination, IFAT serology and LAMP-PCR. The disease severity (clinical score) was staged by using a numeric value derived from 8 clinical and parasitological parameters. Xenodiagnosis was performed on caged dogs exposed for 1.5h to sand-fly bites. The following parameters related to sand flies were examined: blood feeding (% of blood engorged females), promastigote detection (% of promastigote-positive sand flies), promastigote burden, and the promastigote stage maturation (potential transmissibility rate). Statistical relationship between the clinical score and entomological parameters was investigated, as well as the possible correlation between each clinical and laboratory parameters and sand fly infection/infectivity. The severity of clinical score may influence the blood feeding by, and the probability of promastigote detection in, sand flies; skin lesions seem to be the main factor that influences the rate of blood feeding. Promastigote burden is related to IFAT titer, skin lesions and clinical score. All entomological parameters are strongly related among them. This study confirms that both P. perniciosus infection and infectivity are influenced by dog’s clinical condition.